Lung ultrasound-guided treatment for heart failure: An updated meta-analysis and trial sequential analysis - Li, Yan; Ai, Hu; Ma, Na; Li, Peng; Ren, Junhong (Frontiers in Cardiovascular Medicine, 2022)
Background The usefulness of lung ultrasound (LUS) in guiding heart failure (HF) treatment is still controversial. Purpose We aimed to evaluate the usefulness of LUS-guided treatment vs. usual care in reducing the major adverse cardiac event (MACE) rate in patients with HF. Materials and methods We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) identified through systematic searches of MEDLINE, EMBASE, the Cochrane Database, Google Scholar, and SinoMed. The primary outcome was MACEs (a composite of all-cause mortality, HF-related rehospitalization, and symptomatic HF). The required information size was calculated by trial sequential analysis (TSA). Results In total, ten RCTs involving 1,203 patients were included. Overall, after a mean follow-up period of 4.7 months, LUS-guided treatment was associated with a significantly lower risk of MACEs than usual care [relative risk (RR), 0.59; 95% confidence interval (CI), 0.48–0.71]. Moreover, the rate of HF-related rehospitalization (RR, 0.63; 95% CI, 0.40–0.99) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentration (standardized mean difference, –2.28; 95% CI, –4.34 to –0.22) were markedly lower in the LUS-guided treatment group. The meta-regression analysis showed a significant correlation between MACEs and the change in B-line count (p < 0.05). The subgroup analysis revealed that the risk of MACEs was markedly lower in patients aged up to 70 years (RR, 0.54; 95% CI, 0.44–0.67), with a lower rate of atrial fibrillation (< 27.2%) (RR, 0.53; 95% CI, 0.43–0.67), and with a lower NT-proBNP concentration (< 3,433 pg/ml) (RR, 0.51; 95% CI, 0.40–0.64). TSA indicated a lower risk of MACEs with LUS-guided treatment than with usual care among patients with HF (p < 0.05). Conclusion Lung ultrasound seems to be a safe and effective method to guide HF treatment. Systematic review registration [https://inplasy.com/], identifier [INPLASY202220124].